2020
DOI: 10.1186/s12940-020-00663-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between coarse particulate matter and inflammatory and hemostatic markers in a cohort of midlife women

Abstract: Background Exposure to particulate matter air pollution has been associated with cardiovascular disease (CVD) morbidity and mortality; however, most studies have focused on fine particulate matter (PM2.5) exposure and CVD. Coarse particulate matter (PM10–2.5) exposure has not been extensively studied, particularly for long-term exposure, and the biological mechanisms remain uncertain. Methods We examined the association between ambient concentrations of PM10–2.5 and inflammatory and hemostatic makers that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 35 publications
0
10
1
Order By: Relevance
“…Short-term exposure to PM 2.5 was associated with hypomethylation of the genes that encode plasminogen activator inhibitor type I ( SERPINE1 ), coagulation factor III ( F3 ), and coagulation factor II receptor ( F2R ), as well as hypermethylation of coagulation factor II ( F2 ) [38,46,120,142,157]. Within the proteomics literature, short-term exposure to PM 10 and PM 2.5-10 were associated with lower levels of the protein plasminogen activator inhibitor type 1, whereas long-term exposure to PM 2.5 , NO 2 , CO, and O 3 were associated with higher levels of this protein [69,71,73]. Additionally, short-term exposure to PM 2.5 , UFP, BC, NO 2 , and CO were associated with higher levels of coagulation factor III protein (F3) [123,132].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Short-term exposure to PM 2.5 was associated with hypomethylation of the genes that encode plasminogen activator inhibitor type I ( SERPINE1 ), coagulation factor III ( F3 ), and coagulation factor II receptor ( F2R ), as well as hypermethylation of coagulation factor II ( F2 ) [38,46,120,142,157]. Within the proteomics literature, short-term exposure to PM 10 and PM 2.5-10 were associated with lower levels of the protein plasminogen activator inhibitor type 1, whereas long-term exposure to PM 2.5 , NO 2 , CO, and O 3 were associated with higher levels of this protein [69,71,73]. Additionally, short-term exposure to PM 2.5 , UFP, BC, NO 2 , and CO were associated with higher levels of coagulation factor III protein (F3) [123,132].…”
Section: Resultsmentioning
confidence: 99%
“…Short-term exposure to PM 2.5 was associated with hypomethylation of SERPINE1 [142]. Additionally, short-term exposure to PM 10 and PM 2.5-10 was associated with lower levels of the corresponding protein, whereas long-term exposure to PM 2.5 , PM 2.5-10 , NO 2 , CO, and O 3 were associated with higher levels [69,71,73]. Furthermore, short-term BC and NO 2 were associated with higher levels of insulin-like growth factor binding protein 1 and 3, while short-term diesel exhaust was associated with lower levels of insulin-like growth factor binding protein 2 and 14-3-3 protein sigma [79,126].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although our findings are inconsistent with the toxicological research, the results are similar to some of the limited—and largely inconsistent 4 —epidemiological work that has evaluated and these markers, though the similarities differed by blood marker. For example, the cross-sectional 13 and longitudinal 30 studies that have evaluated longer-term and fibrinogen in different cohorts have also found lower levels of fibrinogen with higher concentrations, although all associations were imprecise. For CRP, studies have more consistently found some evidence that higher long-term concentrations led to increases in CRP.…”
Section: Discussionmentioning
confidence: 99%